Helicolenus dactylopterus ... - Bariche, Michel; Fricke, Ronald (Zenodo, 2020)
Helicolenus dactylopterus (Delaroche 1809) —Blackbelly rosefish Taxonomy. First record from Lebanon as Helicolenus dactylopterus (De la Roche 1809) by George et al. (1964: 23); subsequently recorded as Helicolenus dactylopterus (Delaroche) by Mouneimné (1977: 66); as Helicolenus dactylopterus dactylopterus (Delaroche 1809) by Mouneimné (2002: 119); recently recorded as D. dactylopterus by Aguillar et al. (2018: 81). Recent unpublished records from Tyre, Sarafand, Saida, Beirut, Batroun, Tripoli (1998–2019). Distribution. Mediterranean Sea, Sea of Marmara; eastern Atlantic: Norway south to South Africa; southwestern Indian Ocean: South Africa; Greenland; Western Atlantic. Conservation. IUCN: Global (LC: 6 May 2013); Med. (LC: 15 November 2007). Capture and threats: FIT, FIB, unknown. Occurrence: Very common. Low priority for conservation action. ... : Published as part of Bariche, Michel & Fricke, Ronald, 2020, The marine ichthyofauna of Lebanon: an annotated checklist, history, biogeography, and conservation status, pp. 1-157 in Zootaxa 4775 (1) on pages 107-108, DOI: 10.11646/zootaxa.4775.1.1, http://zenodo.org/record/3983887 ...